Comparison between all-on-four and all-on-six treatment concepts on stress distribution for full-mouth rehabilitation using three-dimensional finite element analysis: A biomechanical study - Pandey A.; Durrani F.; Rai S.K.; Singh N.K.; Singh P.; Verma R.; Kumar J. (My University, 2025)
Purpose: The current study intended to provide a comparison of biomechanical behaviors of two different treatment concepts for full-mouth rehabilitation with dental implants placed according to the 'All-on-four' concept and 'All-on-six' concept with analysis of the stress patterns of the implant support system using three-dimensional finite element analysis (FEA). Materials and Methods: The edentulous mandible was treated with two different implant designs. 'All-on-Four' implant placement concept was used in Model 1 with two central axial implants and two distally tilted implants at 17° and in Model 2, 'All-on-Six' concept was applied with six vertically placed implants. Individual vertical and horizontal load of 100 N and oblique load of 141 N at 45° was applied to all implants. To evaluate and compare the results in terms of maximum principal stress, we used FEA. Results: All-on-six showed smaller maximum principal stress values on the cortical bone and implants. However, maximum principal stress values obtained on trabecular bone was smaller in the All-on-four design for vertical and horizontal loading conditions. Conclusions: The All-on-six approach showed more favorable biomechanical behavior. © 2023 Indian Society of Periodontology | Published by Wolters Kluwer - Medknow.